2008
DOI: 10.1063/1.2908867
|View full text |Cite
|
Sign up to set email alerts
|

Polarization resolved luminescence in asymmetric n-type GaAs∕AlGaAs resonant tunneling diodes

Abstract: We have investigated the polarized emission from a n-type GaAs/ AlGaAs resonant tunneling diode under magnetic field. The GaAs contact layer emission shows a large constant negative circular polarization. A similar result is observed for the quantum well, but only when electrons are injected from the substrate, while for inverted biases, the polarization tends to become positive for small voltages and large laser excitation intensities. We believe that the quantum well polarization may be associated to the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…2(b) shows the voltage dependence of the QRs PL intensity and the I(V) characteristics curve. Usually, the PL intensity and I(V) characteristics curve of RTDs are correlated as will be discussed below [10][11] . It was observed that the PL intensity increases with the increase of applied voltage up to about 0.4 V which corresponds to the voltage range that gives important photocurrent values.…”
Section: Samples and Experimental Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…2(b) shows the voltage dependence of the QRs PL intensity and the I(V) characteristics curve. Usually, the PL intensity and I(V) characteristics curve of RTDs are correlated as will be discussed below [10][11] . It was observed that the PL intensity increases with the increase of applied voltage up to about 0.4 V which corresponds to the voltage range that gives important photocurrent values.…”
Section: Samples and Experimental Setupmentioning
confidence: 99%
“…In a simple model, the PL can be given by the product of the electron and hole density. It is well known that the carrier density in the QW increases with voltages associated to resonant tunneling condition [10][11] . Therefore, peaks of PL intensity are expected to be observed around the hole or electron resonance and therefore are correlated to the I(V) characteristics curve.…”
Section: Samples and Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Since hole spin relaxation times are much shorter than electron spin relaxation times, the improvement of spin injection efficiency in those structures is a difficult issue. In the last years, it was also shown that spin-polarization of holes in p-i-p Resonant Tunneling Diodes (RTDs) can be voltage-selected, which makes such device attractive for spintronic applications [9][10][11][12]. A possible improvement of spin-LEDs could thus be obtained by using the resonant tunneling effect in association of a layer of GaMnAs acting as a spin injector in p-i-n RTDs.…”
mentioning
confidence: 99%